Analysis of Sengkarang Watershed Performance with the Addition of River Maintenance Flow Parameters - Sodikin, Wahlul; Juwono, Pitojo Tri; Sholichin, Moh (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
Watershed management plays a crucial role in maintaining water balance and ecosystem sustainability. However, conventional watershed performance assessments often overlook the importance of river maintenance discharge. This study evaluates the hydrological performance of the Sengkarang Watershed by incorporating river maintenance discharge as an additional parameter. The research employs the Tennant method to determine the maintenance flow and the Analytic Network Process (ANP) to weigh its significance. Six expert respondents participated in the weighting process. The study compares the results of the conventional five-parameter assessment with the newly modified six-parameter approach. Findings reveal that the Sengkarang Watershed is concerning, with high fluctuations in flow regimes and annual runoff coefficients. Including river maintenance discharge significantly increases the weight of flood parameters from 2.0% to 4.7%, while the new index for river maintenance discharge contributes 1.8% to the overall assessment. Despite these changes, the watershed remains classified as “Poor,” highlighting the need for further restoration efforts. The study suggests that integrating river maintenance discharge into performance assessments provides a more comprehensive understanding of watershed conditions, supporting better policy formulation for sustainable water resource management.